2010
DOI: 10.1038/ijo.2010.234
|View full text |Cite
|
Sign up to set email alerts
|

Body composition phenotypes in pathways to obesity and the metabolic syndrome

Abstract: Dynamic changes in body weight have long been recognized as important indicators of risk for debilitating diseases. While weight loss or impaired growth can lead to muscle wastage, as well as to susceptibility to infections and organ dysfunctions, the development of excess fat predisposes to type 2 diabetes and cardiovascular diseases, with insulin resistance as a central feature of the disease entities of the metabolic syndrome. Although widely used as the phenotypic expression of adiposity in population and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
195
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(206 citation statements)
references
References 85 publications
3
195
1
7
Order By: Relevance
“…All measured isotope ratios, 2 H/ 1 H and 18 O/ 16 O were normalized to the SMOW/SLAP scale using the internal standards. In the case of the 18 O determinations, the isotope ratios were first expressed relative to PDB for Craig correction 24 before normalization to the SMOW/SLAP scale.…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…All measured isotope ratios, 2 H/ 1 H and 18 O/ 16 O were normalized to the SMOW/SLAP scale using the internal standards. In the case of the 18 O determinations, the isotope ratios were first expressed relative to PDB for Craig correction 24 before normalization to the SMOW/SLAP scale.…”
Section: Study Proceduresmentioning
confidence: 99%
“…2 H analysis was performed using equilibration with hydrogen gas over a platinum catalyst using an Isoprep system (Micromass Ltd, Manchester, UK) coupled to a Sira 10 dual inlet mass spectrometer (VG Isogas Ltd, Middlewich, Cheshire, UK). 18 O enrichment was determined by equilibration with CO 2 gas followed by analysis by continuous flow isotope ratio mass spectrometry (AP 2003, Analytical Precision Ltd, Northwich, Cheshire, UK). Each batch of postdosing urine samples were analysed together with their corresponding basal sample, a gravimetrically diluted sample of the dosing solution and a number of internal standards traceable to the primary reference materials PDB, VSMOW2 and SLAP2 (IAEA, Vienna, Austria).…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the same researchers suggested that weight loss diets make "the lean fatter," because CR-induced feedback signals suppress RMR normalization until the initial fat mass (FM) is fully recovered ("fat-stores memory") [8,7]. The post-diet shift towards an unfavorable body composition may result in repeated dieting attempts and increase the risk of becoming overweight [8].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic slowing, originating from adaptive thermogenesis (AT) in a calorie- recovery and proposed that it is the reason for favorable fat gain after CR [6][7][8].…”
Section: Introductionmentioning
confidence: 99%